Wizard and glass - King, Stephen; aCopyright Paperback Collection (Library of Congress) (New York Pocket Books, 2017)
aRoland the gunslinger and his crew barely escape one world only to slip into another. It is in this other world that Roland relates to his crew a twisted and entertaining tale of his first quest as a gunslinger and the love of his life, Susan Delgado.
Php 100.00
Replacement of Accession No.I-46880
Keywords: aRoland (Fictitious character : King) -- Fiction; aGood and evil -- Fiction; aHorror tales